2021
DOI: 10.3389/fonc.2021.576232
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response, Survival, and Safety of Transarterial Chemoembolization With CalliSpheres® Microspheres Versus Conventional Transarterial Chemoembolization in Hepatocellular Carcinoma: A Meta-Analysis

Abstract: BackgroundDrug-eluting embolic transarterial chemoembolization (DEE-TACE) is an advance in TACE technique. However, at present there is insufficient evidence to support that DEE-TACE is superior to conventional TACE (cTACE) for hepatocellular carcinoma (HCC). The aim of this meta-analysis is to evaluate the efficacy and safety of TACE with CalliSpheres® microspheres (CSM-TACE) compared with cTACE in patients with HCC.Data SourcesPubMed, Embase, Web of Science, CNKI and Wanfang Databases were searched to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…However, a recent meta-analysis of six RCTs did not find significant differences between these two treatments in overall survival or major complications and concluded that the safety and efficacy profile of DEB-TACE was comparable to that of the C-TACE profile [ 30 ]. In another recent meta-analysis, although the study also found comparable overall survival and adverse events between C-TACE and TACE with CalliSpheres ® microspheres (CSM), a polyvinyl alcohol hydrogel microsphere, the pooled analysis revealed that CSM-TACE showed significantly superior efficacy outcomes compared to that in C-TAC-treated patients [ 31 ]. These differences are likely due to heterogeneity between study populations included in the pooled analyses and differences in methodological designs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a recent meta-analysis of six RCTs did not find significant differences between these two treatments in overall survival or major complications and concluded that the safety and efficacy profile of DEB-TACE was comparable to that of the C-TACE profile [ 30 ]. In another recent meta-analysis, although the study also found comparable overall survival and adverse events between C-TACE and TACE with CalliSpheres ® microspheres (CSM), a polyvinyl alcohol hydrogel microsphere, the pooled analysis revealed that CSM-TACE showed significantly superior efficacy outcomes compared to that in C-TAC-treated patients [ 31 ]. These differences are likely due to heterogeneity between study populations included in the pooled analyses and differences in methodological designs.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has considerable strengths over more recently published meta-analyses [ 30 , 31 ]. In our review, we have pooled all available evidence published to date including RCTs and observational studies, whereas Wang et al (2020) included only evidence from randomized trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a Chinese population treated with CalliSpheres, a meta-analysis of 16 studies with 1454 HCC patients by Liang et al showed a higher 1-month and 3-month OR (odds ratio: 2.87, 95% CI: 2.15-3.83 and odds ratio: 3.39, 95%CI: 2.45-4.70) and disease control rate in favor of microsphere treatment (odds ratio: 2.01, 95% CI: 1.37-2.95 and odds ratio: 1.71, 95%CI: 1.14-2.55) [81]. No difference in the PFS, OS, adverse events, or liver function was observed between the two therapies.…”
Section: Ctace Versus Dem-tace: Frenemiesmentioning
confidence: 99%